How marginal is lignite? Two simple approaches to determine price-setting technologies in power markets - Robert Germeshausen; Nikolas Wölfing (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
The parameterisation of energy and climate policies often depends on the technology, which is price-setting in electricity markets. We propose two simple approaches to determine marginal technologies in electricity wholesale from available data. Both approaches are complementary, computationally lightweight, and do not require specific software. Identification is based upon assumptions which are commonly used in more complex energy system models and which vary according to the approach. We illustrate the relevance of our approach for consistent policy parameterization with an example from the compensation scheme for indirect emission costs from the EU Emissions Trading Scheme (EU ETS). We find that the current policy design severely overweighs CO2 emissions from lignite power plants in the CWE power market.
Keywords: Q41; Q48; Q58; 330; marginal technology; price formation; power market; indirect cost compensation